2008
DOI: 10.1051/0004-6361:200809653
|View full text |Cite
|
Sign up to set email alerts
|

Star cluster versus field star formation in the nucleus of the prototype starburst galaxy M 82

Abstract: We analyse high-resolution Hubble Space Telescope/Advanced Camera for Surveys imaging of the nuclear starburst region of M 82, obtained as part of the Hubble Heritage mosaic made of this galaxy, in four filters (Johnson-Cousins equivalent B, V, and I broad bands, and an Hα narrow-band filter), as well as subsequently acquired U-band images. We find a complex system of ∼150 star clusters in the inner few 100 pc of the galaxy. We do not find any conclusive evidence of a cluster-formation epoch associated with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 91 publications
(145 reference statements)
1
37
0
Order By: Relevance
“…Barker et al 2008). As input parameter, the threshold value for detection is related to the number of sources found in applying this procedure.…”
Section: Source Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barker et al 2008). As input parameter, the threshold value for detection is related to the number of sources found in applying this procedure.…”
Section: Source Selectionmentioning
confidence: 99%
“…The youngest sample thus encompasses the time of the most recent starburst in the galaxy's nucleus, 4-6 Myr ago (e.g., Barker et al 2008), while the intermediate-age sample may be associated with the burst of cluster formation induced by the last M81/M82 flyby (e.g., de Grijs et al 2001;Smith et al 2007). Lim et al (2013) separated their sample of more than 1100 clusters by region, and found that each region (specifically, the galaxy's disk, its halo, the nuclear region, and region M82-B) exhibits a different cluster formation history.…”
Section: Parameter Determinationmentioning
confidence: 99%
“…The situation for the SMC is less straightforward, although Rafelski & Zaritsky (2005) provide tentative evidence that the cluster and field-star age distributions may also be significantly different in this system (see also Gieles, Lamers & Portegies Zwart 2007). Similarly, the observed disparities between the cluster and field-star age distributions in the (dwarf) starburst galaxies NGC 1569 (Anders et al 2004) and M82 (Barker, de Grijs & Cerviño 2008) seem to offer evidence in support of a decoupling between star cluster and field-star formation. If confirmed, this would be consistent with the view that massive star cluster formation requires special conditions, e.g., large scale gas flows, in addition to the presence of dense gas (cf.…”
Section: Introductionmentioning
confidence: 98%
“…Yun et al (1993) compared the disk H i with optical maps, and found a large amount of gas being channeled into the core of the galaxy over the last 200 Myr due to the tidal encounter with its large spiral neighbor galaxy M 81. Ages derived from super star clusters (SSCs) in optical and near-IR images are ∼50 Myr (de Grijs et al 2001), ∼30-100 Myr (Rieke et al 1993;Barker et al 2008), ∼4-6, and 10-30 Myr (Förster-Schreiber et al 2003;Smith et al 2006;Melo et al 2005). The corresponding estimates of the average star formation rate (SFR) over the 200 Myr period is roughly about 10 M yr −1 .…”
Section: Introductionmentioning
confidence: 99%